3(3z-1)-3(3-2z)=9

Simple and best practice solution for 3(3z-1)-3(3-2z)=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(3z-1)-3(3-2z)=9 equation:


Simplifying
3(3z + -1) + -3(3 + -2z) = 9

Reorder the terms:
3(-1 + 3z) + -3(3 + -2z) = 9
(-1 * 3 + 3z * 3) + -3(3 + -2z) = 9
(-3 + 9z) + -3(3 + -2z) = 9
-3 + 9z + (3 * -3 + -2z * -3) = 9
-3 + 9z + (-9 + 6z) = 9

Reorder the terms:
-3 + -9 + 9z + 6z = 9

Combine like terms: -3 + -9 = -12
-12 + 9z + 6z = 9

Combine like terms: 9z + 6z = 15z
-12 + 15z = 9

Solving
-12 + 15z = 9

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 15z = 9 + 12

Combine like terms: -12 + 12 = 0
0 + 15z = 9 + 12
15z = 9 + 12

Combine like terms: 9 + 12 = 21
15z = 21

Divide each side by '15'.
z = 1.4

Simplifying
z = 1.4

See similar equations:

| h=-0.05x^2+x+3 | | 13p+17q+p-6q-3p= | | y=-8x(x-2) | | 3p-13=11 | | M-35=21whatism | | -5x/3=5/2 | | 6x=22.5 | | x-3/7x | | -2=4x-6 | | 4+2p=12 | | 6(z-3)=3(z+1)+3 | | 72/8=48/12 | | 5x-15=27-2x | | -8x-18=30+-2x | | -2x+26=2x+10 | | 5x+4=-3x+13 | | 3n+12=24 | | 6+2(Z-3)=-5z+3 | | 11m+5n-5m+7n= | | 56=10log(x) | | 2m=16-9 | | 3c+6=33 | | 14x-3=9x-15 | | -3+6k=9 | | 62+3y=36 | | 36=2.4/(.12-x) | | 1/6-1/3=2/3 | | -4t-7(2t-5)-11=-12 | | 2x+6y-20=0 | | (2x)(x+10)+110=360 | | 5(2x+3)+-3(2+x)=22 | | 2x^2+2y^2-10x-18y=0 |

Equations solver categories